A case study for heat and mass transfer of viscous fluid flow in double layer due to ciliated channel. (May 2023) - Fatima, Nahid; Sooppy Nisar, Kottakkaran; Shaheen, Sidra; Arain, Muhammad Bilal; Ijaz, Nouman; Muhammad, Taseer
Abstract: The present study is a measurement of the thermal and mass transfer of a two-layered flow of viscous fluid induced by cilia motion under the effect of buoyancy forces through a channel. Cilia are mostly of two classes: motile and non-motile cilia for locomotion and sensory processing. Cilia tissue cells are epithelia lining the lungs that sweep away liquids or solids, and organisms that have cilia are protozoans that use them for movements are the examples. The ciliary apparatus is related to cell cycle movement and proliferation, and cilia display an energetic fragment in human and animal development and in ordinary life. The fluid is considered to be incompressible, and layers of fluid do not mix with each other. The fluid flow for mass and thermal transfer is modelled in wave and fixed frame. Solutions for temperature, velocity of fluid, and concentration profile are obtained using a well-known method, namely the Homotopy Perturbation Method (HPM), by the computation software "MATHEMATICA". The behavior of emerging parameters is shown graphically in the results section. Graphical results can be analyzed for the temperature and velocity profile, which are extreme in the inner layer for both fluid and concentration distribution and are highest at the external layers of fluid. It is the first study not examined in the literature.